L’état actuel des études stratégiques : À propos des hérissons et des renards - Sigler, John (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1989)
Western writers and thinkers can be divided into two categories : those who are hedgehogs and emphasize one central vision and unity of the world, and those who are foxes who emphasize diversity, separateness and uniqueness. My argument in this article is that much of the debate about the proper place of strategic studies in the larger field of international relations stems from this major distinction. The strategists tend to be hedgehogs who take one paradigm, one set of applications and one set of political commitments and make a great deal out of it. I will argue that there is also merit to understanding that there are foxes as well, who would place the central vision of the strategists in a larger context of other truths, other applications, and broader commitments.